When Placebic Information Differs From Real Information : Cognitive and Motivational Bases of Mindful Reactions to Informational Social Influence - Lee, Eun-Ju (Communication Research, 2005)
The present experiments investigated how individuals’ cognitive thinking styles and the influence agent’s sex would affect the extent to which people mindfully respond to informational social influence. In Study 1, participants played a trivia game with an ostensible partner via computer and were presented with either real information that provided a rationale for the partner’s choice or placebic information that merely restated accompanying self-confidence ratings in verbal format. As predicted, real information was more likely than was placebic information to elicit conformity (a) among high compared to low rationals, (b) when the partner expressed the highest ambiguity (50% confident), and (c) when a female compared to a male character represented the partner, albeit only among men. By employing more direct measures of information processing, reaction time and perceived validity of the partner’s claims, Study 2 confirmed that greater acceptance of real rather than placebic information stemmed from more effortful message decoding.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwMjA1Mjc5MzUx